The deubiquitinase USP11 regulates cell proliferation and ferroptotic cell death via stabilization of NRF2 USP11 deubiquitinates and stabilizes NRF2 - Meng, Chunjie; Zhan, Jun; Chen, Delin; Shao, Genze; Zhang, Hongquan; Gu, Wei; Luo, Jianyuan (Oncogene, 2021)
The transcription factor nuclear factor (erythroid-derived 2)-like 2 (NRF2) plays a key role in cancer progression and is tightly regulated by the proteasome pathway. E3 ligases that mediate NRF2 ubiquitination have been widely reported, but the mechanism of NRF2 deubiquitination remains largely unclear. Here, we identified ubiquitin-specific-processing protease 11 (USP11) in NRF2 complexes and confirmed an interaction between these two proteins. We further found that USP11 deubiquitinates NRF2; this modification stabilizes NRF2. Functionally, USP11 depletion contributes to the suppression of cell proliferation and induction of ferroptotic cell death due to ROS-mediated stress, which can be largely abrogated by overexpression of NRF2. Finally, immunohistochemical staining of USP11 and NRF2 was performed using a lung tissue microarray, which revealed that USP11 is highly expressed in patients with NSCLC and positively correlated with NRF2 expression. Together, USP11 stabilizes NRF2 and is thus an important player in cell proliferation and ferroptosis.